IDENTIFIKASI MEKANISME TRANSMISI KEBIJAKAN MONETER SALURAN UANG DAN SALURAN SUKU BUNGA DI INDONESIA - Deswita Herlina (Jurnal Ekonomi-Qu, 2018)
ABSTRACTThe purpose of this research is to identify the effectiveness of monetary policy transmission mechanism throught both quantity channel (Monetarist Approach) and interest rate channel (Keynesian Approach) in Indonesia during the period of the first quartelly of 2000 to the third quartelly of 2014. The effectiveness of the monetary policy transmission is measured by the time lag and the strength of the variables in order to respond monetary policy shocks. The datais collected from Economic and Financial Statistics in Indonesia (SEKI). This research uses vector error correction model (VECM) to analysis the research model, and set the transmission of monetary policy conducted by Bank Indonesia as the research object. Stationerity test, unit of root test, optimum lag, Johansen cointegration test, impulse response function and varian ofdecomposition are conducted before analysze the VECM model. In addtition, the research result shows that the transmission of monetary policy through interst rate channel with capital cost effect is more effective than through interest rate consumption channel and money channel.